Broken Promises in Public Housing: Analyzing Functional Failure of Juwana Rusunawa, Pati - Maharani, Ardiyanti Julia (Indonesian Journal of Agrarian Law, 2025)
Rusunawa Juwana is a vertical housing project built in 2016 with a total budget of Rp28.9 billion, which came from the allocation of central government funds through the Ministry of Public Works and Public Housing (PUPR). The project was designed to be a housing solution for low-income communities, especially those affected by regular flooding in the Pati region of Central Java, with the hope of improving the quality of life of residents through safe, decent and affordable housing. However, within six years of its operation, the condition of the building suffered from various serious and significant damages, especially leaks on the roof and walls that caused mould and mildew, which not only disturbed the comfort of the residents but also had an impact on their health. This situation has led to low public interest in occupying the residential units, despite the low rent. This article aims to analyse in depth the causes of the malfunction of Rusunawa Juwana, using a descriptive qualitative approach sourced from secondary data, including media reports and relevant public documents. The analysis revealed that these failures were caused by a number of crucial factors, including poor technical planning and supervision in the development process, weak post-development monitoring systems that should ensure building quality and safety, and the lack of maintenance budgets allocated by local governments after management responsibilities were handed over from the central government.